The influence of the store environment characteristics toward impulse buying, positive emotional response of consumers as a mediation - Anita Larasati; Zakky Fahma Auliya (Journal of Economics and Business Research (JUEBIR), 2023)
This study aims to determine the influence of store environment characteristics on impulse purchases with positive emotional response responses of consumers as mediation variables. This sampling used purposive sampling using quantitative methods with survey methods using questionnaires totaling 100 respondents with the criteria of visitors to Matahari Department Store Solo Grand Mall who had purchased fashion products. This study used path analysis to test the hypothesis, while data processing was done with the help of the IBM SPSS Statistics 25 application The results showed that the characteristics of the store environment have a positive and significant influence on the positive emotional response of consumers. So is consumers' positive emotional response to impulse purchases. This study also shows the influence given by store environment characteristics on impulse purchases with positive emotional responses of consumers as mediating variables. As for the characteristics of the store environment impulse purchases do not have a positive and significant influence.